Factores de riesgo asociados a bronquiolitis en lactantes en el Hospital Regional de Loreto, durante el periodo 2021 – 2023 - Nonaka Reyna, Alfert Hector (2024)
Introduction: Bronchiolitis is an acute infectious disease of viral etiology with diffuse inflammatory condition of the lower respiratory tract (bronchioles), having an acute presentation. It is one of the main reasons for hospitalization in patients in their first year of life, thus causing expense and concern for the health system in the world. OBJECTIVE: To determine the risk factors associated with bronchiolitis in infants at the Regional Hospital of Loreto during the period 2021 - 2023. MATERIAL AND METHODS: An analytical observational study of the case control type will be carried out, with a prospective design that will collect data in a time interval from July 2021 to December 2023. The study universe will consist of all infants admitted to the department of pediatrics of the HRL "Felipe Santiago Arriola Iglesias" with the diagnosis of bronchiolitis during the mentioned period. The statistical analysis will be descriptive and will include the presentation of absolute figures, frequencies and/or averages, as well as standard deviations to describe the characteristics of infants with bronchiolitis. Nonparametric tests, such as the Mann-Whitney U test or Chi-square, will be used as necessary to examine differences between data and relationships between cases and controls. In addition, a binary logistic regression will be performed to understand the impact of various factors on the presence or absence of bronchiolitis. The work will be reviewed and approved by the ethics committee belonging to UNAP. The confidentiality and privacy of the information collected will be maintained, following the guidelines established in the Declaration of Helsinki of 2013. RESULTS: They will be obtained according to the completion of the schedule for data analysis. CONCLUSIONS: They will be carried out once the results have been obtained.